Day of the Dragon King - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series, 1998)
The magic treehouse takes Jack and Annie back two thousand years to ancient China where they must find the original copy of an old legend before the Imperial Library is burned down by the evil Dragon King.